(untitled) (The International Journal for Scientific Research, 2026)
The Objective of the Research is to identify the role of secondary school principals in developing administrative work in secondary schools in the center of Nineveh Governorate. The descriptive approach was used using the survey method and the study sample included (235) physical education teachers in secondary schools in the center of Nineveh Governorate. To obtain the data, the scale (Al-Manaamah, 2005) was adopted and applied after the scientific conditions of validity and reliability were met. Through the arithmetic mean, standard deviation, percentage, Spearman-Brown equation, Gitman equation, and Cronbach’s alpha coefficient. The researcher has drawn several conclusions, the most important is that the level of the role played by the school principal in developing the administrative work in his school was at a high level in the secondary schools in the center of Nineveh Governorate. The researcher recommends that the necessity of showing sufficient interest in school administrations by those in charge of educational institutions and providing them with the latest developments in developing administrative work and adopting scientific methods in all areas related to secondary school administrations.